INTERAKSI OBAT PADA PASIEN RAWAT INAP HIPERTENSI DI RSUP PERSAHABATAN PERIODE TAHUN 2015 - Islam, Zainul; Vitasari, Atika; Ridwan, Muhammad Arif (Prosiding Seminar Nasional Berseri, 2020)
Hypertension can cause various complications such as cardiovascular disease, stroke, diabetes mellitus, and kidney failure. To overcome these complications, patients are given polypharmacy therapy which has the potential to cause drug interactions. This study aims to determine the incidence of drug interactions in hypertensive inpatients at the Friendship Hospital in the period of 2015. This study was a descriptive study conducted using a purposive sampling technique retrospectively using secondary data, namely medical records of hypertensive inpatients. Drug interaction studies were carried out theoretically based on literature studies using the book Drug Interaction Facts 2014. The results showed that of 174 hypertensive patients 141 patients (81.03%) had the potential to experience drug interactions with a total of 1,443 cases. Most drug interactions were significance level 3 in 383 cases (26.54%), pharmacodynamic mechanisms in 554 cases (38.39%).